CLINICAL EFFICIENCY OF VACCINATION, ERDOSTEINE AND PULMONARY REHABILITATION IN THE PREVENTION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE EXACERBATIONS - A. V. Budnevskiy; E. S. Ovsyannikov; A. V. Pertsev; S. A. Kozhevnikova (Туберкулез и болезни лёгких, 2016)
Goal of the study: to evaluate the clinical efficiency of anti-influenza vaccination, erdosteine and pulmonary rehabilitation for prevention of exacerbations in COPD patients.Materials and methods. 108 patients suffering from COPD of medium severity (average age 50.48 ± 0.88 years old) and receiving standard therapy for their main condition were enrolled into the study. The results were evaluated in 12 months by the software titled Management System for Treatment and Diagnostics of Those Suffering from Asthma and Chronic Obstructive Pulmonary Disease (Pulmosys).Results. This set of measures demonstrated confidently high clinical efficiency: anti-influenza vaccination, erdosteine and pulmonary rehabilitation compared to standard therapy, and compared to vaccination and pulmonary rehabilitation with standard therapy. Clinical efficiency manifested through confident reduction in the number of exacerbations and admissions to hospital, positive changes in the clinical signs of COPD, confident reduction of the system biomarkers' level, increased tolerance to physical load, and enhancement in the life quality of the patients.